Cmentarzysko i osada kultury łużyckiej w Leśnie, gm. Brusy - Walenta, Krzysztof (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
In the years 1975-1976 the Excavation Expedition of Łódź University, conducting studies on the settlement complex from the Roman period at Leśno, performed salvage studies on the Lusatian culture cemetery and settlement. There were discovered 26 cremated burials, 20 hollows, and 11 ceramics clusters. In most cases these were hollow burials and only burial No. 18 was an urn burial. In three cases the burial hollows were covered with stone pavements. The discovered settlement objects give rise to many interpretation problems. Only hollow No. 1 could perform housing functions, while the remaining ones must have been auxiliary objects. From among mobile relics, the ceramic findings are most numerous. In their number the richest findings include bowls, barrel-shaped vessels, and small spherical vessels with cylindric necks. The entire finding may be dated back to the end of the Bronze Age.